Pengaruh Komisaris Independen, Komite Audit, dan Kompleksitas Operasi Perusahaan Terhadap Audit Delay - Ikhsan Romadhan; Meta Nursita (Masyarakat Ekonomi Syariah Bogor, 2025)
This researchs aims to determine the effect of independent commissioners, audit committees, and the complexity of company operations on audit delay. The research uses a sample of companies in the Properties & Real Estate sector listed on the Indonesia Stock Exchange from 2018 to 2023. The sampling method employed in this study is purposive sampling, utilizing Eviews 13 for data analysis. The data sources for this research are quantitative data derived from annual financial reports, with a sample of 17 companies and observations over 6 years, resulting in a total sample size of 102. The analysis technique used is panel data regression. The results indicate that, simultaneously, independent commissioners, audit committees, and the complexity of company operations have an impact on audit delay. Partially, the findings show that the audit committee and the complexity of company operations do not significantly affect audit delay, while the independent commissioners have a significant effect on audit delay.